The Use of Special Knowledge by Defense in Economic Crime Investigations - A. E. Galinskaya (Теория и практика судебной экспертизы, 2016)
The paper examines actions taken by defense when financial and economic assessment is warranted in the course of economic crime investigation; the order of commission of financial and economic assessment by the investigator or court in order to establish a fact of bankruptcy fraud; capacity of the defense to contest expert testimony; errors committed by forensic economists when conducting financial and economic assessment in the criminal investigation of bankruptcy fraud; ways to prevent forensic expert mistakes; the wording of conclusions in the expert witness report; problems associated with the use of uncertified methodologies of forensic assessment; attitudes demonstrated by various courts within the Russian justice system towards the use of special knowledge by defense economic crime investigations, including the position of the European Court of Human Rights (ECtHR) in light of the European Convention; procedural and non-procedural documentation used by the defense in economic crime investigations.